SABER-School Finance : Data Collection Instrument - World Bank (Washington, DC, 2015)
The aim of the SABER-school finance initiative is to collect, analyze and disseminate comparable data about education finance systems across countries. SABER-school finance assesses education finance systems along six policy goals: (i) ensuring basic conditions for learning; (ii) monitoring learning conditions and outcomes; (iii) overseeing service delivery; (iv) budgeting with adequate and transparent information; (v) providing more resources to students who need them; and (vi) managing resources efficiently. SABER-school finance will document how education is financed by national, subnational, local governments, and schools.